¿Sería posible mantener un orden mundial multipolar? Enfoque analítico de un sistema internacional liderado por varias superpotencias - MORENO VILCHEZ, Covadonga (Journal of the Spanish Institute for Strategic Studies, 2024)
In the current globalised and changing world order, the viability of a multipolar international system led by several superpowers can be questioned for its potential impact on maintaining stability. Hence this dissertation examines the challenges posed by globalisation, technological progress, and the emergence of new international actors in relation to changing dynamics that can undermine the existing world order.The analysis draws on the perspectives of both realist and neorealist schools to evaluate the stability of the multipolar system, and the coexistence of multiple superpowers is studied through historical and theoretical frameworks, taking into account factors such as military capabilities, economic influence, and the spread of universal principles. The study explores potential stability conditions in a multipolar system and addresses issues such as the Alliance paradox and the Security Dilemma. Said theoretical considerations are complemented by a historical analysis of the distribution of power after the industrial revolution, which emphasises the transition from great powers to superpowers, contending that a multipolar system led by superpowers may face challenges in maintaining order due to heightened rivalry, the security dilemma, and the potential emergence of violent non-state actors.
Keywords: Globalisation; Mutual deterrence; Security; Superpowers; Hegemony; World order; Multipolarity; Non-state actors